Features of the planimetric organization of the endocrine part of the pancreas in hypertensive rats of the SHR line - T. V. Ivanenko (Zaporozhye State Medical University, 2022)
Analysis of the endocrine structure of the pancreas and assessment of its degree of heterogeneity is key to assessing such important physiological parameters as islet endocrinocyte mass in healthy people or functional reserve of β-cells in patients with type 1 and type 2 diabetes. The aim of the study is to perform a comparative planimetric analysis of pancreatic islets of normotensive Wistar rats and hypertensive SHR rats, using the method of double immunofluorescent staining of endocrinocytes. Materials and methods. The study was performed on the pancreas of SHR and Wistar rats. Insulin and glucagon in the islets of the pancreas were determined by immunofluorescence. The immunofluorescence reaction was studied with an AxioImager-M2 fluorescent microscope. Results. Planimetric analysis showed the presence of pancreatic islets of all types in the pancreatic tissue of SHR and Wistar rats. The number of single endocrinocytes in SHR hypertensive animals was 2.3 times higher (P < 0.001), and the number of giant islets was 34.2 % higher (P < 0.001), than in normotensive Wistar rats. The presence of regions in some endocrinocytes, that show immunoreactivity to both hormones at once - insulin and glucagon. Such areas were present in islets of all types of both rat lines, however, the total rates in hypertensive rats of the SHR line were 21.8 % lower (P < 0.001), than in normotensive rats of the Wistar line. Conclusions. Planimetric analysis showed, that the pancreatic islets in normotensive Wistar rats and hypertensive SHR rats occupy 1.4 % of the cross-sectional area of the pancreas. In hypertensive rats the SHR line in the gland by 16.9 % larger total area of the material immunoreactive to insulin. In contrast to Wistar rats, the number of single α-endocrinocytes in the pancreas of hypertensive SHR rats was significantly increased.